GENERALIZED MINIMAX FRACTIONAL PROGRAMMING PROBLEMS WITH GENERALIZED NONSMOOTH $(F, ALPHA, RHO, D, THETA)$-UNIVEX FUNCTIONS - Jayswal, A.; Stancu-minasian, I.; Ahmad, I.; Kummari, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
The aim of this paper is to establish the sufficient optimality conditions for a class of nondifferentiable multiobjective generalized minimax fractional programming problems involving univex functions. Subsequently, we apply the optimality condition to formulate a dual model and prove weak, strong and strict converse duality theorems.